Unsteady flow-induced vibration of the slider in a commercial hard disk drive - Toh, Jeffrey See Ren. (2013)
The Flow-Induced Vibration (FIV) of Head Gimbal Assembly (HGA) occurred as a result of turbulent airflow within the commercial hard disk drive HDD. Therefore, this project aims to conduct an investigation through numerical simulation to determine the characteristics of FIV of the HGA.